2016
DOI: 10.1371/journal.pone.0168456
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased RNA Shotgun Metagenomics in Social and Solitary Wild Bees Detects Associations with Eukaryote Parasites and New Viruses

Abstract: The diversity of eukaryote organisms and viruses associated with wild bees remains poorly characterized in contrast to the well-documented pathosphere of the western honey bee, Apis mellifera. Using a deliberate RNA shotgun metagenomic sequencing strategy in combination with a dedicated bioinformatics workflow, we identified the (micro-)organisms and viruses associated with two bumble bee hosts, Bombus terrestris and Bombus pascuorum, and two solitary bee hosts, Osmia cornuta and Andrena vaga. Ion Torrent semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 53 publications
8
43
0
Order By: Relevance
“…This approach allowed us to search for novel viruses, begin to determine the distribution of these viruses (and viral families) across the world, and begin to evaluate the extent to which A. mellifera and wild bee populations share these viruses. As in other studies [28,29], we identified several viruses that share sequence homology to plant viruses and thus may be the result of contamination, but given that these were found in multiple populations and locations, it raises the question of whether or not these viruses may use bees as hosts.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…This approach allowed us to search for novel viruses, begin to determine the distribution of these viruses (and viral families) across the world, and begin to evaluate the extent to which A. mellifera and wild bee populations share these viruses. As in other studies [28,29], we identified several viruses that share sequence homology to plant viruses and thus may be the result of contamination, but given that these were found in multiple populations and locations, it raises the question of whether or not these viruses may use bees as hosts.…”
Section: Introductionsupporting
confidence: 61%
“…Positive sense RNA ((+)ssRNA) viruses are the most common type of virus that have been identified in bees thus far, with a vast majority of the viruses possessing this genome architecture. Most of these viruses belong to the viral order Picornavirales (including DWV, BQCV, IAPV, and SBV), but recently additionally studies have added to the list of viral orders that infect bees, including Tymovirales [6,29]. Here we have identified novel virus sequences that share sequence homology with three (+)ssRNA virus families, Dicistroviridae, Secoviridae, and Tymoviridae.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations